Effect of two aqueoua extracts of Myrtus communis and Thuja orientalis in growth and development of Musca domestica L. ovary - Najem Shalmoon; Safa Mohammed Mahmoud (College of Education for Pure Sciences, 2009)
Abstract Several preliminary experiments were carried out to detect the effects of eight aqueous plant extracts on the growth and development of the ovaries and their follicles. The two best extracts were chosen and used in this study. The results of the microscopical preparations and statistical analysis clearly show that the sublethal concentrations (0.5, 1, 1.5, 2.5, 5, 10, 15, %20) of the leaves extract of Myrtus communis and of the fruits extract of Thuja orientalis, which were chosen and used against the second instars of housefly, have shown a highly significant inhibitory effect on the growth and development of the ovaries and ovarian follicles when compared with those of control specimens. Not only this, but some concentrations have reduced the number of the follicles and have sometimes led to their degradation and disappearance either partially or completely. Therefore, the aqueous plant extracts are preferred on those of alcoholic and acetonic ones because the former are easy to prepare, cheep, with highly significant effects.